The Role of Transposable Elements in Sexual Development - Chiang, Vic Shao-Chih; DeRosa, Holly; Park, Jin Ho; Hunter, Richard G. (Frontiers in Behavioral Neuroscience, 2022)
Up to 50% of most mammalian genomes are made up of transposable elements (TEs) that have the potential to mobilize around the genome. Despite this prevalence, research on TEs is only beginning to gain traction within the field of neuroscience. While TEs have long been regarded as “junk” or parasitic DNA, it has become evident that they are adaptive DNA and RNA regulatory elements. In addition to their vital role in normal development, TEs can also interact with steroid receptors, which are key elements to sexual development. In this review, we provide an overview of the involvement of TEs in processes related to sexual development- from TE activity in the germline to TE accumulation in sex chromosomes. Moreover, we highlight sex differences in TE activity and their regulation of genes related to sexual development. Finally, we speculate on the epigenetic mechanisms that may govern TEs’ role in sexual development. In this context, we emphasize the need to further the understanding of sexual development through the lens of TEs including in a variety of organs at different developmental stages, their molecular networks, and evolution.